Life skills, employability and training for disadvantaged youth: Evidence from a randomized evaluation design - Pablo Ibarrarán; Laura Ripani; Bibiana Taboada; Juan Miguel Villa; Brígida García (Institute for the Study of Labor (IZA), 2012)
This paper presents an impact evaluation of a revamped version of the Dominican youth training program Juventud y Empleo. The paper analyzes the impact of the program on traditional labor market outcomes and on outcomes related to youth behavior and life style, expectations about the future and socio-emotional skills. In terms of labor market outcomes, the program has a positive impact on job formality for men of about 17 percent and there is also a seven percent increase in monthly earnings among those employed. However, there are no overall impacts on employment rates. Regarding non-labor market outcomes, the program reduces teenage pregnancy by five percentage points in the treatment group (about 45 percent), which is consistent with an overall increase in youth expectations about the future. The program also has a positive impact on non-cognitive skills as measured by three different scales. Scores improve between 0.08 and 0.16 standard deviations with the program. Although recent progress noted in the literature suggests that socio-emotional skills increase employability and quality of employment, the practical significance of the impacts is unclear, as there is only weak evidence that the life skills measures used are associated to better labor market performance. This is an area of growing interest and relevance that requires further research.
Keywords: J24; J64; O15; O17; 330; impact evaluation; Dominican Republic; youth training programs; labor market outcomes; employment; life skills; Jugendliche; Berufsbildung; Arbeitsmarktpolitik; Wirkungsanalyse; Qualifikation; Berufliche Integration; Dominikanische Republik